The Rhetoric of Semantic Structure in Qur’anic Expression - fatih, merzouk (El Omda in Linguistics and Discourse Analysis, 2023)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-(--header-height)" dir="auto" data-turn-id="6a78dbf4-4143-4415-add4-6cd9023cdfff" data-turn-id-container="6a78dbf4-4143-4415-add4-6cd9023cdfff" data-testid="conversation-turn-15" data-scroll-anchor="false" data-turn="user"> *]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:38ea93c2-f9b9-4bbb-9c07-4854f35c29e2-7" data-turn-id-container="request-WEB:38ea93c2-f9b9-4bbb-9c07-4854f35c29e2-7" data-testid="conversation-turn-16" data-scroll-anchor="false" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="4d4516b9-948b-4ceb-988b-ce12b1376a28" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> This study addresses a fundamental aspect of linguistics in general and rhetoric in particular, especially when dealing with Qur’anic expression, which is characterized by precision of structure, stylistic beauty, and coherence of composition. However, linguistic structure varies according to different levels: some belong to syntax, others to morphology, while this study focuses on the semantic level. In essence, semantics is built upon syntactic structures and their interrelations, as well as morphological forms and their meanings. Syntactic constructions are loaded with meanings that reveal their intended purpose, while morphological patterns carry embedded significations that disclose their deeper implications. Without these distinctions, the miraculous nature of Qur’anic expression, particularly its textual coherence and rhetorical organization, would not be evident. This is what rendered the Qur’anic discourse inimitable and beyond the capability of the most eloquent Arab speakers and masters of rhetoric.